Identification of novel bacterial urease inhibitors through molecular shape and structure based virtual screening approaches. Issue 27 (22nd April 2020) - Imran, Muhammad; Waqar, Saba; Ogata, Koji; Ahmed, Mahmood; Noreen, Zobia; Javed, Sundus; Bibi, Nazia; Bokhari, Habib; Amjad, Asma; Muddassar, Muhammad
Abstract : The enzyme urease is an essential colonizing factor of the notorious carcinogenic pathogen Helicobacter pylori ( H. pylori ), conferring acid resistance to the bacterium. Abstract : The enzyme urease is an essential colonizing factor of the notorious carcinogenic pathogen Helicobacter pylori ( H. pylori ), conferring acid resistance to the bacterium. Recently, antibiotic resistant strains have emerged globally with little to no alternative treatment available. In this study we propose novel urease inhibitors capable of controlling infection by H. pylori and other pathogenic bacteria. We employed hierarchal computational approaches to screen new urease inhibitors from commercial chemical databases followed by in vitro anti-urease assays. Initially ROCS shape-based screening was performed using o -chloro-hippurohydroxamic acid followed by molecular docking studies. Out of 1.83 million compounds, 1700 compounds were retrieved based on having a ROCS Tanimoto combo score in the range of values from 1.216 to 1.679. These compounds were further screened using molecular docking simulations and the 100 top ranked compounds were selected based on their Glide score. After structural classification of the top ranked compounds, eight compounds were selected and purchased for biological assays. The plausible binding modes of the most active compounds were also confirmed using molecular dynamics (MD) simulations. Compounds 1, 2 and 3 demonstrated good urease inhibitory properties (IC50 = 0.32, 0.68 and 0.42 μM) compared to the other compounds. Enzyme kinetic studies revealed that compounds 1 and 3 are competitive inhibitors while 2 is a mixed type inhibitor of the urease enzyme. Cell based urease inhibition and MTT assay showed that these compounds blocked H. pylori urease activity, affecting bacterial growth and acid tolerance.